Ice cream as functional food: a review of health-promoting ingredients in the frozen dairy products - Mohammed, Nameer Khairullah; Badrul Khair, Muhammad Firdaus; Ahmad, Nurul Hawa; Meor Hussin, Anis Shobirin (Wiley-Blackwell, 2022)
Ice cream has been selected as a good carrier of beneficial effects through the health-promoting component incorporated into the product to meet the needs of functional food. The majority of people in the globe adore ice cream because it has distinct texture and sensory features. Ice cream is a promising carrier for the unhindered distribution of bioactive elements due to its composition, colloidal form, and low-temperature system. The development of functional ice cream has consolidated numerous health-promoting ingredients such as probiotics, prebiotic, synbiotic, and natural antioxidants (e.g., polyphenols). In this review, recent advances in the attempts of developing alternative ice cream formulation and functional ice cream (a product supplemented or fortified with bioactive substances) are presented: the highlighted contents encompass the aspects that include—defining the bioactive component with its beneficial effect, strategies for the successful integration with potential hurdles during the product manufacture, ideal consumption model with possible side-effect, and current scenario of the functional ice cream development.